Subversion of Immunity by Leishmania amazonensis Parasites: Possible Role of Phosphatidylserine as a Main Regulator - Joao Luiz Mendes Wanderley; Jaqueline França Costa; Valéria Matos Borges; Marcello Barcinski (Journal of Parasitology Research)
Leishmania amazonensis parasites cause progressive disease in most inbred mouse strains and are associated with the development of diffuse cutaneous leishmaniasis in humans. The poor activation of an effective cellular response is correlated with the ability of these parasites to infect mononuclear phagocytic cells without triggering their activation or actively suppressing innate responses of these cells. Here we discuss the possible role of phosphatidylserine exposure by these parasites as a main regulator of the mechanism underlying subversion of the immune system at different steps during the infection.